2017
DOI: 10.1186/s13071-017-2027-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative expression profile of microRNAs in Anopheles anthropophagus midgut after blood-feeding and Plasmodium infection

Abstract: Background Anopheles anthropophagus is one of the major vectors of malaria in Asia. MicroRNAs (miRNAs) play important roles in cell development and differentiation as well as in the cellular response to stress and infection. In a former study, we have investigated the global miRNA profiles in relation to sex in An. anthropophagus. However, the miRNAs contributing to the blood-feeding and infection with Plasmodium are still unknown.MethodsHigh-throughput sequencing was performed to identify miRNA profiles of An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…sRNA-seq also allows for the detection of low-abundance miRNA transcripts and yields data on novel miRNA nucleotide sequence [ 27 ]. sRNA-seq differs from standard mRNA sequencing by the addition of a size selection step during the library preparation where the small RNAs are isolated from larger RNA molecules through a gel electrophoresis step [ 28 , 29 ]. There are inherent biases of the sRNA-seq technique including the effects that GC content and adaptor/barcode sequences can have on the efficiency of cDNA synthesis prior to sequencing (see recent reviews for more details [ 30 , 31 ]).…”
Section: Micrornasmentioning
confidence: 99%
See 2 more Smart Citations
“…sRNA-seq also allows for the detection of low-abundance miRNA transcripts and yields data on novel miRNA nucleotide sequence [ 27 ]. sRNA-seq differs from standard mRNA sequencing by the addition of a size selection step during the library preparation where the small RNAs are isolated from larger RNA molecules through a gel electrophoresis step [ 28 , 29 ]. There are inherent biases of the sRNA-seq technique including the effects that GC content and adaptor/barcode sequences can have on the efficiency of cDNA synthesis prior to sequencing (see recent reviews for more details [ 30 , 31 ]).…”
Section: Micrornasmentioning
confidence: 99%
“…As many mosquito species have the ability to vector human pathogens such as the arboviruses; dengue, Zika, and chikungunya, as well as Plasmodium parasites, understanding the role of miRNAs during the immune responses to these pathogens can be vital in developing novel vector control strategies (see recent reviews [ 22 , 33 ]). A recent study examined the miRNA expression in midguts of Anopheles anthropophagus fed either on non-infected or Plasmodium -infected blood [ 29 ]. In the non-infected blood experiment, nine significantly upregulated and 10 significantly downregulated miRNAs were identified, with one (miR-92a) previously reported as induced upon blood feeding in Aedes aegypti [ 29 , 34 ].…”
Section: Micrornasmentioning
confidence: 99%
See 1 more Smart Citation
“…While mechanisms are known for how gene expression fluctuates during a blood meal at the transcriptional level (Attardo et al 2005), the mechanisms of post-transcriptional regulation of gene expression are largely unknown. As a much-needed step to address this gap in knowledge, the vector biology field is currently exploring post-transcriptional regulation of mRNA transcripts and its effects on female mosquito physiology by studying a class of small RNAs called microRNAs (miRNAs) (Mead and Tu 2008; Li et al 2009; Gu et al 2013; Hu et al 2015; Skalsky et al 2010; Biryukova et al 2014; Liu et al 2017; Jain et al 2014; Castellano et al 2015; Liu et al 2014b; Jain et al 2015; Allam et al 2016; Lampe and Levashina 2018; Fu et al 2017; Liu et al 2014a; Zhao et al 2017; Zhang et al 2016; Lucas et al 2015a; Lucas et al 2015b; Ling et al 2017; Zhang et al 2017; Akbari et al 2013).…”
mentioning
confidence: 99%
“…Deep sequencing studies in Aedes albopictus , Aedes aegypti , Culex quinquefasciatus , Anopheles stephensi , Anopheles anthropophagus , Anopheles funestus , and An. gambiae demonstrate (i) evolutionarily conserved miRNAs, (ii) mosquito-specific miRNAs, and lastly (iii) novel miRNAs (Mead and Tu 2008; Li et al 2009; Gu et al 2013; Hu et al 2015; Skalsky et al 2010; Biryukova et al 2014; Liu et al 2017; Jain et al 2014; Castellano et al 2015; Liu et al 2014b; Jain et al 2015; Allam et al 2016; Akbari et al 2013; Zhang et al 2017). By microarray technology, a recent study in Anopheles gambiae found midgut- and ovary-enriched miRNAs (Lampe and Levashina 2018).…”
mentioning
confidence: 99%